Clinical reasoning in the emergency medical services: an integrative review - Ulf Andersson; Hanna Maurin Söderholm; Birgitta Wireklint Sundström; Magnus Andersson Hagiwara; Henrik Andersson (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2019)
Abstract Clinical reasoning is the process of gathering and understanding information conducted by clinicians in the emergency medical services (EMS) so as to make informed decisions. Research on clinical reasoning spans several disciplines, but a comprehensive view of the process is lacking. To our knowledge, no review of clinical reasoning in the EMS has been conducted. Aim The aim was to investigate the nature, deployment, and factors influencing EMS clinicians’ clinical reasoning by means of a review. Method Data was collected through searches in electronic databases, networking among research teams, colleagues and friends, “grey literature,” and through ancestry searches. A total of 38 articles were deemed eligible for inclusion and were analyzed using descriptive thematic analysis. The analysis resulted in an overarching finding - namely, the importance for EMS clinicians to adjust for perceived control in unpredictable situations. Within this finding, 3 themes emerged in terms of EMS clinicians’ clinical reasoning: (1) maintaining a holistic view of the patient; (2) keeping an open mind; and (3) improving through criticism. Seven subthemes subsequently emerged from these three themes. Results This review showed that EMS clinicians’ clinical reasoning begins with the information that they are given about a patient. Based on this information, clinicians calculate the best route to the patient and which equipment to use, and they also assess potential risks. They need to be constantly aware of what is happening on the scene and with the patient and strive to control the situation. This striving also enables EMS clinicians to work safely and effectively in relation to the patient, their relatives, other clinicians, associated organizations, and the wider community. A lack of contextually appropriate guidelines results in the need for creativity and forces EMS clinicians to use “workarounds” to solve issues beyond the scope of the guidelines available. In addition, they often lack organizational support and fear repercussions such as litigation, unemployment, or blame by their EMS or healthcare organization or by patients and relatives. Conclusion Clinical reasoning is influenced by several factors. Further research is needed to determine which influencing factors can be addressed through interventions to minimize their impact on patient outcomes.